The Influence of Attractions, Service, e-WOM on Revisit Decisions with Satisfaction Mediation and Digital Promotion Moderation - Aldien Ramadhan; Ida Bagus Cempena; Endah Budiarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research investigates the impact of tourist attractions, service quality, and electronic word of mouth (e-WOM) on visitors’ intention to revisit Sendang Tourism Village, located in Tulungagung, East Java. Additionally, the study explores the function of visitor satisfaction as an intermediary variable and digital promotion as a potential moderator. The study emerged from the concern over fluctuating visitor numbers despite Sendang’s rich appeal in terms of natural landscapes, cultural heritage, and traditional charm. A quantitative method was applied, making use of a structured data collection process structured survey distributed to 138 individuals who had previously visited the site. The data were examined through Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate and interpret the relationships between the research variables both the direct and mediated pathways between variables. This technique was chosen for its ability to explain complex relationships within behavioral research. The results reveal that tourist attraction, service quality, and e-WOM have a significant positive influence on revisit intention. Furthermore, tourist satisfaction was shown to act as a bridging variable between these predictors and return visits. On the other hand, digital promotion was not found to significantly moderate these effects. This indicates that digital marketing, while useful, may not independently boost visitor return rates unless paired with strong destination quality and positive visitor experiences. From a conceptual standpoint, the study contributes to tourism marketing discourse by incorporating both mediation and moderation into the revisit intention framework. In practical terms, the findings highlight the need for tourism managers to prioritize visitor satisfaction and enhance the core travel experience. Digital tools should complement rather than replace genuine service improvements and compelling destination features to effectively encourage repeat tourism.